Analisis Sektor Unggulan dan Perubahan Struktur Ekonomi di Kabupaten Mimika Tahun 2017-2021 - Selpi; Iek, Mesak; Kaiwai, Hans Z. (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2026)
This research aims to identify leading sectors and changes in the economic structure without mining in Mimika Regency in 2017–2021. The data used in this research is secondary data on Gross Regional Domestic Product (GRDP) according to business fields on the basis of constant prices in 2010, with data years 2017–2021. The analysis tools used are Location Quotient, Shift Share Analysis, and Klassen Typology. The results of the location quotient analysis without mining found that there are 8 basic (leading) sectors, namely: 1) the electricity and gas procurement sector; 2) the wholesale and retail trade sector; 3) the car and motorcycle repair sector; 4) the transportation and warehousing sector; 5) the accommodation and food and drink provision sector; 6) the information and communication sector; 6) the financial services and insurance sector; 7) the real estate sector; and 8) the corporate services sector. Furthermore, the results of the shift share analysis show that, in aggregate, there have been structural changes in the economic sector in Mimika Regency during 2017–2021, where the entire economic sector is classified as progressive and growing faster than the same sector in Papua Province. Meanwhile, according to the Klassen Typology analysis, the economic sector in Mimika Regency, which is classified as a developed sector and is growing rapidly, consists of 8 sectors, including: 1) the electricity and gas procurement sector; 2) the wholesale and retail trade sector; 3) car and motorcycle repair; 4) the transportation and warehousing sector; 5) the accommodation and food and drink provision sector; 6) the information and communication sector; 6) the financial services and insurance sector; 7) the real estate sector; and 8) the corporate services sector. The regional government needs to continue to encourage the process of structural change in the economic sector in Mimika Regency so that sectors that have the potential to develop can grow more quickly. The emergence of new sectors is a good thing for the regional economy. In the future, it is necessary to carry out analysis with valid data in order to find changes in the regional economic structure appropriately so that it can support a more optimal regional economy. Keywords: Leading sectors and changes in economic structure without mining